Preparation of oxidized Zn–In nanostructures for electrochemical non-enzymatic cholesterol sensing. (15th November 2021) - Khan, Shakil; Rasheed, Muhammad Asim; Shah, Attaullah; Mahmood, Arshad; Waheed, Abdul; Karim, Shafqat; Khan, Maaz; Ali, Ghafar
Abstract: In this work, impact of hydrothermal oxidation time on electrodeposited Zn–In films and their electrochemical non-enzymatic cholesterol sensing has been investigated. The oxidized Zn–In films have been prepared by a two-step method. That is the co-electrodeposition of Zn–In film on copper substrate followed by its hydrothermal oxidation in de-ionized (DI) water at 95 °C. The oxidation time has been varied as 01, 03, 06 and 12 h. The XRD patterns of oxidized Zn–In films revealed the polycrystalline ZnO and Zn2 In2 O5 phases. The field emission scanning electron microscopy (FE-SEM) showed the morphological evolution from nanoplates to nanorods as a result of increasing the oxidation time. The photoluminescence spectra of oxidized Zn–In nanostructures depicted that the visible light emission diminishes with increasing the oxidation time. The responses of oxidized Zn–In electrodes towards different cholesterol concentration (01 μM – 9 mM) have been recorded by cyclic voltammetry (CV) and amperometry in phosphate buffer solution without using any enzymes. CV measurements for these materials exhibited progressively better sensitivity for cholesterol with increasing oxidation time. Electrode based on Zn–In films oxidized for 12 h exhibited largest amperometric responses toward cholesterol with a sensitivity of 81 μA mM −1 −cm −2 in the concentration range of 0.5 mM–9 mM. A response current for as low as 01 μM cholesterol concentration have been recorded.